Implementasi dan Problematika Pemberlakuan Kurikulum 2013 PAUD Terhadap Pembelajaran PAUD (Studi Di Kabupaten Sumenep dan Pamekasan) - Musayyadah Musayyadah; Norma Gupita; Danang Prastyo (Institut Agama Islam Negeri Madura, 2021)
Curriculum implementation should be able to embody the vision, mission and the purpose of national education gradually, but in fact faced the problem and challange. It also applies to curriculum implementation 2013. On learning early childhood education is still have some problem. The purpose of this research is giving knowledge about the curriculum 2013 and explained the problem of faced by the school, the teacher and head of the school. Methods used in this study is to use the descritive kualitatif. The results of 20 intituation early chlidhood education in Sumenep and Pamekasan found problem that diverse.